NILLTPFN likuma prasību ievērošana Latvijas grāmatvedības ārpakalpojumu uzņēmumos - Karlsone, Sanita (Latvijas Universitāte, 2020)
Maģistra darba mērķis ir izpētīt noziedzīgi iegūtu līdzekļu legalizācijas un terorisma un proliferācijas finansēšanas novēršanas likuma prasības, aktualitātes un praksi attiecībā uz grāmatvedības ārpakalpojumu uzņēmumiem Latvijā. Praktiskajā daļā veicot dažādu avotu analīzi, autore nonāca pie secinājumiem, ka NILLTFNL prasību izpilde sagādā problēmas daudziem Latvijas grāmatvedības ārpakalpojumu uzņēmumiem- grūti izsekot likuma grozījumiem, subjektīva likuma izpratne, grūti noteikt savus un klienta riskus, un identificēt aizdomīgus darījumus. Autore piedāvā risinājumus, kā varētu uzlabot likuma prasību ievērošanu.

The aim of the master's thesis is to study the requirements, topicalities and practice of the law on the prevention of money laundering and terorism and proliferation financing in relation to accounting outsourcing companies in Latvia. Analyzing various sources in the practical part the author came to the conclusion that compliance with requirements of the law on the prevention of money laundering and terorism and proliferation financing poses serious problems for many accounting outsourcing companies in Latvia - difficult to track changes in the law, subjective understanding of the law, difficulties in identifying own risks as well as ones concerning customers, problems to identify suspicious transactions and insufficient financial resources to execute all these requirements. The author offers several solutions how to improve compliance with the law. Keywords: money laundering prevention, money laundering and terorism and proliferation financing prevention law, outsourced accountant, internal control system, customer due diligence.
Compliance with requirements of law on the prevention of money laundering and terrorism and proliferation financing in accounting outsourcing companies in Latvia
Keywords: Ekonomika; noziedzīgi iegūtu līdzekļu legalizācijas novēršana; Noziedzīgi iegūtu līdzekļu legalizācijas un terorisma un proliferācijas finansēšanas novēršanas likums; ārpakalpojuma grāmatvedis; iekšējā kontroles sistēma; klienta izpēte